2023
DOI: 10.1002/lpor.202201001
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Metasurface‐Based Surface‐Plasmon Lenses

Abstract: A device that can couple propagating light into surface plasmon polaritons (SPPs) focused into a small region is highly desired for on-chip photonics applications (e.g., energy-harvesting, sensing, etc.). However, current technologies suffer from large device footprint, low working efficiency, and insufficient light-manipulation freedom. Here, a generic approach for designing plasmonic lenses to generate predesigned vector SPP vortices with high efficiencies is established. Constructed with a set of meta-atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Note that the convert efficiency of BPPs can be further increased by optimizing the plasmonic lens with metasurfaces. [ 41 ] Figure 4c,d shows the scattering spectrum of two example of the hybrid system, where the size of the cylinder is the same as that in Figure 4a,b, respectively. In both cases it's obviously observed that a narrow resonant peak overlaps with another broad peak, which corresponds to the high‐ and low‐Q mode, respectively.…”
Section: Design Strategy For Qbic‐induced High‐q Modesmentioning
confidence: 99%
“…Note that the convert efficiency of BPPs can be further increased by optimizing the plasmonic lens with metasurfaces. [ 41 ] Figure 4c,d shows the scattering spectrum of two example of the hybrid system, where the size of the cylinder is the same as that in Figure 4a,b, respectively. In both cases it's obviously observed that a narrow resonant peak overlaps with another broad peak, which corresponds to the high‐ and low‐Q mode, respectively.…”
Section: Design Strategy For Qbic‐induced High‐q Modesmentioning
confidence: 99%
“…Mn 4+ -activated oxide phosphors generally exhibit high chemical stability and strong red to deep red luminescence under ultraviolet (UV) light excitation, and they can be prepared using cheap starting materials via eco-friendly processes. Hence, these phosphors are very popular candidates for applications requiring red light and hence have been investigated for warm white-light emission and wide-gamut backlighting based on phosphor-converted white light-emitting diodes ( pc-WLEDs) [1][2][3][4][5][6] as well as for indoor plant cultivation 7,8 and thermometry. 3,9 As is well known, under a crystal field environment with an O h symmetry, the five d orbitals in a transition metal (TM) ion split into three-fold t 2g and two-fold e g levels.…”
Section: Introductionmentioning
confidence: 99%
“…A metasurface, a kind of two-dimensional metamaterial, is composed of subwavelengthresolved meta-atoms that can be designed to enable multidimensional manipulation of the polarization, phase, and amplitude of the optical field [1][2][3][4][5][6]. By controlling the geometry, orientation, and composition of these meta-atoms, the metasurface can be used in a variety of applications, such as optical imaging, information processing, energy harvesting, and optical sensing [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%